Precision Limits of Tissue Microstructure Characterization by Magnetic Resonance Imaging - Zwick, Analía Elizabeth (2020)
Characterization of microstructures in living tissues is one of the keys to diagnosing early stages of pathology and understanding disease mechanisms. However, the extraction of reliable information on biomarkers based on microstructure details is still a challenge, as the size of features that can be resolved with noninvasive magnetic resonance imaging (MRI) is orders of magnitude larger than the relevant structures. Here we derive from quantum information theory the ultimate precision limits for obtaining such details by MRI probing of water-molecule diffusion. We show that currently available MRI pulse sequences can be optimized to attain the ultimate precision limits by choosing control parameters that are uniquely determined by the expected size, the diffusion coefficient, and the spin relaxation time T2. By attaining the ultimate precision limit per measurement, the number of measurements and the total acquisition time may be drastically reduced compared to the present state of the art. These results are expected to open alternative avenues towards unraveling diagnostic information by quantitative MRI.